Tinjauan Investasi Perlindungan Laut dan Kawasan Pengelolaan Perikanan ( KPP ) : Studi Kasus Taman Nasional Bunaken dengan Analisis Cost-Benefit dan SWOT - Salsabila Florenza; Yorriezka Asta Pebriani; Catherina Kristina Usior (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
Investment in marine protection and Fisheries Management Areas (FMAs) is crucial for maintaining the sustainability of the global marine ecosystem. This paper aims to evaluate investment in marine protection and FMAs using Bunaken National Park as a case study. The Cost-Benefit and SWOT analysis approaches are employed to assess the efficiency, effectiveness, and challenges faced in marine protection and fisheries management efforts in this area. Through this review, various costs and benefits of the investment are evaluated, while strengths, weaknesses, opportunities, and threats associated with the implementation of the investment are also identified. The results of this analysis provide insights into the economic feasibility, potential success, and strategies that can be implemented to enhance the sustainability of the marine ecosystem and the welfare of local communities in Bunaken National Park.